Pregunta
upstudy study bank question image url

5. Complete the following. a) Simplify: i) \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \) ii) \( \left(m+\frac{1}{m}\right)^{2} \). b) If \( m+\frac{1}{m}=2 \), calculate the value of: i) \( m^{2}+\frac{1}{m^{2}} \) ii) \( m^{3}+\frac{1}{m^{3}} \)

Ask by Curry Stewart. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

**a) Simplifications:** - **i)** \( \left(m + \frac{1}{m}\right)\left(m^{2} - 1 + \frac{1}{m^{2}}\right) = m^{3} + \frac{1}{m^{3}} \) - **ii)** \( \left(m + \frac{1}{m}\right)^{2} = m^{2} + 2 + \frac{1}{m^{2}} \) **b) Given \( m + \frac{1}{m} = 2 \):** - **i)** \( m^{2} + \frac{1}{m^{2}} = 2 \) - **ii)** \( m^{3} + \frac{1}{m^{3}} = 2 \)

Solución

Let's solve each part of the problem step-by-step. --- ### **Problem 5** **a) Simplify:** **i) \( \left(m + \frac{1}{m}\right)\left(m^{2} - 1 + \frac{1}{m^{2}}\right) \)** To simplify the expression, we'll expand the product by multiplying each term in the first parenthesis with each term in the second parenthesis: \[ \begin{align*} \left(m + \frac{1}{m}\right)\left(m^{2} - 1 + \frac{1}{m^{2}}\right) &= m \cdot m^{2} + m \cdot (-1) + m \cdot \frac{1}{m^{2}} \\ &\quad + \frac{1}{m} \cdot m^{2} + \frac{1}{m} \cdot (-1) + \frac{1}{m} \cdot \frac{1}{m^{2}} \\ &= m^{3} - m + \frac{1}{m} + m - \frac{1}{m} + \frac{1}{m^{3}}. \end{align*} \] Now, combine like terms: \[ m^{3} - m + m + \frac{1}{m} - \frac{1}{m} + \frac{1}{m^{3}} = m^{3} + \frac{1}{m^{3}}. \] **Answer:** \[ \left(m + \frac{1}{m}\right)\left(m^{2} - 1 + \frac{1}{m^{2}}\right) = m^{3} + \frac{1}{m^{3}}. \] --- **ii) \( \left(m + \frac{1}{m}\right)^{2} \)** To simplify the square of a binomial, use the formula \((a + b)^2 = a^2 + 2ab + b^2\): \[ \begin{align*} \left(m + \frac{1}{m}\right)^{2} &= m^{2} + 2 \cdot m \cdot \frac{1}{m} + \frac{1}{m^{2}} \\ &= m^{2} + 2 + \frac{1}{m^{2}}. \end{align*} \] **Answer:** \[ \left(m + \frac{1}{m}\right)^{2} = m^{2} + 2 + \frac{1}{m^{2}}. \] --- **b) Given that \( m + \frac{1}{m} = 2 \), calculate the value of:** **i) \( m^{2} + \frac{1}{m^{2}} \)** Start with the square of \( m + \frac{1}{m} \): \[ \begin{align*} \left(m + \frac{1}{m}\right)^{2} &= m^{2} + 2 \cdot m \cdot \frac{1}{m} + \frac{1}{m^{2}} \\ &= m^{2} + 2 + \frac{1}{m^{2}}. \end{align*} \] Given that \( m + \frac{1}{m} = 2 \), square both sides: \[ 2^{2} = m^{2} + 2 + \frac{1}{m^{2}} \\ 4 = m^{2} + 2 + \frac{1}{m^{2}}. \] Subtract 2 from both sides to find \( m^{2} + \frac{1}{m^{2}} \): \[ 4 - 2 = m^{2} + \frac{1}{m^{2}} \\ 2 = m^{2} + \frac{1}{m^{2}}. \] **Answer:** \[ m^{2} + \frac{1}{m^{2}} = 2. \] --- **ii) \( m^{3} + \frac{1}{m^{3}} \)** To find \( m^{3} + \frac{1}{m^{3}} \), use the identity: \[ \left(m + \frac{1}{m}\right)^{3} = m^{3} + 3m + 3\cdot\frac{1}{m} + \frac{1}{m^{3}}. \] Rearrange to solve for \( m^{3} + \frac{1}{m^{3}} \): \[ m^{3} + \frac{1}{m^{3}} = \left(m + \frac{1}{m}\right)^{3} - 3\left(m + \frac{1}{m}\right). \] Given \( m + \frac{1}{m} = 2 \): \[ m^{3} + \frac{1}{m^{3}} = 2^{3} - 3 \cdot 2 = 8 - 6 = 2. \] **Alternatively**, since \( m + \frac{1}{m} = 2 \), solve for \( m \): Multiply both sides by \( m \): \[ m^{2} + 1 = 2m \\ m^{2} - 2m + 1 = 0 \\ (m - 1)^{2} = 0 \\ m = 1. \] Then, \[ m^{3} + \frac{1}{m^{3}} = 1^{3} + \frac{1}{1^{3}} = 1 + 1 = 2. \] **Answer:** \[ m^{3} + \frac{1}{m^{3}} = 2. \] --- ### **Final Summary** **a) Simplifications:** - **i)** \(\left(m + \dfrac{1}{m}\right)\left(m^{2} - 1 + \dfrac{1}{m^{2}}\right) = m^{3} + \dfrac{1}{m^{3}}\) - **ii)** \(\left(m + \dfrac{1}{m}\right)^{2} = m^{2} + 2 + \dfrac{1}{m^{2}}\) **b) Given \( m + \dfrac{1}{m} = 2 \):** - **i)** \(m^{2} + \dfrac{1}{m^{2}} = 2\) - **ii)** \(m^{3} + \dfrac{1}{m^{3}} = 2\)

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

The Deep Dive

To tackle these mathematical expressions, let's break them down step by step. a) Simplification: i) To simplify \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \): - We recognize that \( m^2 - 1 + \frac{1}{m^2} = (m^2 + \frac{1}{m^2}) - 1 \). - From the identity \( (m+\frac{1}{m})^2 = m^2 + 2 + \frac{1}{m^2} \), we find \( m^2+\frac{1}{m^2} = (m+\frac{1}{m})^2 - 2 \). - Thus, we expand \( (m+\frac{1}{m}) \left((m^2 + \frac{1}{m^2}) - 1\right) \). - Finally, substituting and simplifying leads to a clean expression. ii) To simplify \( \left(m+\frac{1}{m}\right)^{2} \): - Using the same identity as before, we get \( (m+\frac{1}{m})^{2} = m^2 + 2 + \frac{1}{m^2} \). b) Given \( m+\frac{1}{m}=2 \): i) To find \( m^{2}+\frac{1}{m^{2}} \): - From \( (m+\frac{1}{m})^2 = 2^2 = 4 \), we have \( m^2 + 2 + \frac{1}{m^2} = 4 \). - Therefore, \( m^2 + \frac{1}{m^2} = 4 - 2 = 2 \). ii) To find \( m^{3}+\frac{1}{m^{3}} \): - Use the identity \( m^3 + \frac{1}{m^3} = (m+\frac{1}{m})(m^2+\frac{1}{m^2}) - (m+\frac{1}{m}) \). - Substituting our known values, we get \( 2(2) - 2 = 4 - 2 = 2 \). Enjoy simplifying and calculating! 🧠✨

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad